2002
DOI: 10.1016/s1567-5394(01)00168-2
|View full text |Cite
|
Sign up to set email alerts
|

Scanning probe microscopic imaging of guanine on a highly oriented pyrolytic graphite electrode

Abstract: Guanine adsorbed onto a highly oriented pyrolytic graphite electrode was studied by MAC-Mode Atomic Force Microscopy (AFM), and the electrochemical behaviour of the guanine layer was investigated with Electrochemical AFM. Guanine adsorbs spontaneously, without forming a well-packed structure, into nucleation spots, which are stable with time and cover the surface uniformly and almost completely. The process of guanine adsorption and nucleation can be controlled and the effect of altering the exposure time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 4 publications
2
12
0
1
Order By: Relevance
“…28 An anisotropic patterned assembly of single- and double-stranded DNA on graphene nanoribbons (GNRs) was ascribed to the donor–acceptor interactions, wherein electric dipole and van der Waals (vdW) coupling facilitates the charge transfer between DNA and GNRs. 34 Atomic force microscopy (AFM) imaging of G molecules on freshly cleaved HOPG 35 showed that G molecules condense in small nuclei without the formation of an ordered assembly. Likewise, molecular packing of adenine on a (0001) graphite surface was found to be commensurate with the graphite surface.…”
Section: Introductionmentioning
confidence: 99%
“…28 An anisotropic patterned assembly of single- and double-stranded DNA on graphene nanoribbons (GNRs) was ascribed to the donor–acceptor interactions, wherein electric dipole and van der Waals (vdW) coupling facilitates the charge transfer between DNA and GNRs. 34 Atomic force microscopy (AFM) imaging of G molecules on freshly cleaved HOPG 35 showed that G molecules condense in small nuclei without the formation of an ordered assembly. Likewise, molecular packing of adenine on a (0001) graphite surface was found to be commensurate with the graphite surface.…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies have verified the experimental results [23] . However reports on direct application of nucleic acids or their fragments in the field of electronics and batteries are limited [24–27] . We have previously reported an Li guanine complex as an electrolyte displaying high Li‐ion transference number and conductivity [27] …”
Section: Introductionmentioning
confidence: 55%
“…[23] However reports on direct application of nucleic acids or their fragments in the field of electronics and batteries are limited. [24][25][26][27] We have previously reported an Li guanine complex as an electrolyte displaying high Li-ion transferencenumber andc onductivity. [27] Earlier reports have highlighted the significance of nucleobases in electronic conductivity owing to their p-electron overlap.…”
Section: Introductionmentioning
confidence: 99%
“…The 8-oxoG is the G base oxidation product at the C8 position, and presents several tautomeric forms in aqueous solution, the most stable being the 6,8-diketo I tautomer, with an oxo group at the C8 position and a H atom at the N7 positions, as shown in Scheme 4 [37][38][39][40]. The electrochemical oxidation mechanisms of G and guanosine at carbon electrodes, with the formation of 8-oxoG and 8-oxodG, have been extensively studied under different experimental conditions [2,4,10,11,13,[16][17][18]29,32,36,[41][42][43][44][45]. The oxidation of DNA nucleosides, deoxyadenosine (dA), deoxyguanosine (dG), deoxythymidine (dT) and deoxycytidine (dC), occurs at the same potentials as the nucleotides, GMP, AMP, thymidine monophosphate (TMP) and cytidine monophosphate (CMP), as shown in Figure 1, with dG and GMP at Ep ~ +0.95 V, dA and AMP at Ep ~ +1.21 V, dT and TMP at Ep ~ +1.41 V, and dC and CMP at Ep ~ +1.56 V (vs. Ag/AgCl, 3 M KCl), at pH = 7.4, being shifted to more positive potentials, compared with the bases' oxidation potentials [32].…”
Section: Electrochemical Detection Of 8-oxodg and 28-dha Biomarkers mentioning
confidence: 99%